2020
DOI: 10.1001/jamasurg.2020.4569
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Robotic vs Laparoscopic Ventral Hernia Repair With Intraperitoneal Mesh

Abstract: IMPORTANCE Despite rapid adoption of the robotic platform for ventral hernia repair with intraperitoneal mesh in the United States, there is no level I evidence comparing it with the traditional laparoscopic approach. This randomized clinical trial sought to demonstrate a clinical benefit to the robotic approach.OBJECTIVE To determine whether robotic approach to ventral hernia repair with intraperitoneal mesh would result in less postoperative pain. DESIGN, SETTING, AND PARTICIPANTSA registry-based, single-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 46 publications
(86 reference statements)
2
51
0
Order By: Relevance
“…One non-matched study 24 found a decreased intraoperative complication rate with robotic surgery when the RD was calculated. Intraoperative complication rates for robotic and laparoscopic VHR ranged between 1 and 6 per cent among the three studies 21 , 30 , 36 reporting this outcome and were no different between the approaches ( Table 6 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…One non-matched study 24 found a decreased intraoperative complication rate with robotic surgery when the RD was calculated. Intraoperative complication rates for robotic and laparoscopic VHR ranged between 1 and 6 per cent among the three studies 21 , 30 , 36 reporting this outcome and were no different between the approaches ( Table 6 ).…”
Section: Resultsmentioning
confidence: 93%
“…The remaining two RCTs compared robotic with laparoscopic intraperitoneal onlay mesh (IPOM) repair ( Table 2 ). One 20 was multi-institutional and included 123 patients, and the other 21 included 75 patients at a single institution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials are needed to show that the potential benefits, i.e., shorter operation time, earlier discharge, and less postoperative pain, motivate the costs associated with the robot device. A recently published randomized controlled trial showed that the outcome was equal after robot-assisted and conventional laparoscopic hernia repair, but to greater costs with robot-assisted repair (10). The trial was, however, based on intraperitoneal mesh in both groups, which limits the relative advantage of robotassisted repair.…”
Section: Discussionmentioning
confidence: 99%
“…If patients can be discharged the same day, it will be difficult to beat, as costs will be even lower. It may also be a generation thing [29] . The younger surgical generation has not known the struggles and fights to move laparoscopy from open surgery.…”
mentioning
confidence: 99%